The Ayahuasca ritual: Peruvian national cultural heritage and its possible integration into the primary health system (2021)
On June 24, 2008, the Peruvian Government declared the “knowledge and traditional uses of Ayahuasca practiced by native Amazonian communities” as National Cultural Heritage. The inspiration that led to this important achievement was to protect the ritual use of the Ayahuasca brew as traditionally practiced for centuries by Amazonian indigenous communities, including its intangible ritual component, the knowledge of the healers and the healers themselves, while also favoring the protection of the environment and the sustainability of the plant resources involved. In the last couple of decades, the mechanisms of action of Ayahuasca and its therapeutic potential in several fields have been investigated in depth. Nevertheless, thirteen years after the enactment of this declaration, regulations that can offer a concrete protection are still pending, while we observe increasing commercial pressure and risks associated with the irresponsible use of Ayahuasca and other psychoactive plants in the context of shamanic tourism.